(3eTGcd hMdhds - (3YUGe(B, (3GdTGYQs ((3GdEScfOQjI(B:s (3ecJHI heWHYI GdETYGY GdafjI(B,s, 2005)
(3EOGQI GdELJeGYGJ(B-(3JWhjQ GdCOGA(B-(3cJGHI GdJbQjQ(B-(3EOGQI GdhbJs
Keywords: (3EOGQI GdhbJs; (3GdELJeGYs; (3GdJbQjQs